12-Oxo-Phytodienoic Acid Acts as a Regulator of Maize Defense against Corn Leaf Aphid. Issue 4 (14th January 2019) - Varsani, Suresh; Grover, Sajjan; Zhou, Shaoqun; Koch, Kyle G.; Huang, Pei-Cheng; Kolomiets, Michael V.; Williams, W. Paul; Heng-Moss, Tiffany; Sarath, Gautam; Luthe, Dawn S.; Jander, Georg; Louis, Joe
Abstract : 12-Oxo-phytodienoic acid promotes enhanced callose accumulation and heightened maize resistance against aphids. Abstract: The corn leaf aphid (CLA; Rhopalosiphum maidis ) is a phloem sap-sucking insect that attacks many cereal crops, including maize ( Zea mays ). We previously showed that the maize inbred line Mp708, which was developed by classical plant breeding, provides enhanced resistance to CLA. Here, using electrophysiological monitoring of aphid feeding behavior, we demonstrate that Mp708 provides phloem-mediated resistance to CLA. Furthermore, feeding by CLA on Mp708 plants enhanced callose deposition, a potential defense mechanism utilized by plants to limit aphid feeding and subsequent colonization. In maize, benzoxazinoids (BX) or BX-derived metabolites contribute to enhanced callose deposition by providing heightened resistance to CLA. However, BX and BX-derived metabolites were not significantly altered in CLA-infested Mp708 plants, indicating BX-independent defense against CLA. Evidence presented here suggests that the constitutively higher levels of 12-oxo-phytodienoic acid (OPDA) in Mp708 plants contributed to enhanced callose accumulation and heightened CLA resistance. OPDA enhanced the expression of ethylene biosynthesis and receptor genes, and the synergistic interactions of OPDA and CLA feeding significantly induced the expression of the transcripts encoding Maize insect resistance1-Cysteine Protease, a key defensive protein against insect pests, in Mp708 plants. Furthermore, exogenous application of OPDA on maize jasmonic acid-deficient plants caused enhanced callose accumulation and heightened resistance to CLA, suggesting that the OPDA-mediated resistance to CLA is independent of the jasmonic acid pathway. We further demonstrate that the signaling function of OPDA, rather than a direct toxic effect, contributes to enhanced CLA resistance in Mp708.